2005
DOI: 10.1002/ajh.20507
|View full text |Cite
|
Sign up to set email alerts
|

Ikaros increases normal apoptosis in adult erythroid cells

Abstract: Ikaros is a critical transcriptional regulator of hematopoietic cell differentiation. In addition to its effects on the lymphoid system and hematopoietic stem-cell compartment, we have previously shown that Ikaros is also required for normal erythroid development. In this report, we compare Ikaros-dependent gene expression in erythroid cells of mice lacking the Ikaros protein with that of normal mice in purified adult bone-marrow erythroid cells (BMRC). Gene expression, measured by Affymetrix microarray analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
10
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 34 publications
(57 reference statements)
0
10
0
Order By: Relevance
“…GATA-1 and Ikaros were both reported to influence EryC homeostasis (17,38,42,45,51,55,56,59,62). GATA-1 regulates a number of genes in EryC; however, to date only a few Ikaros-regulated genes have been identified in these cells (3,5,45).…”
Section: Expression Levels Of Hes1 During Erythroid Cell Differentiatmentioning
confidence: 99%
See 2 more Smart Citations
“…GATA-1 and Ikaros were both reported to influence EryC homeostasis (17,38,42,45,51,55,56,59,62). GATA-1 regulates a number of genes in EryC; however, to date only a few Ikaros-regulated genes have been identified in these cells (3,5,45).…”
Section: Expression Levels Of Hes1 During Erythroid Cell Differentiatmentioning
confidence: 99%
“…GATA-1 and Ikaros were both reported to influence EryC homeostasis (17,38,42,45,51,55,56,59,62). GATA-1 regulates a number of genes in EryC; however, to date only a few Ikaros-regulated genes have been identified in these cells (3,5,45). While an expression array revealed that the absence of Ikaros causes variable expression of different genes controlling apoptosis in EryC (45), the precise effect of Ikaros on erythroid gene regulation has been studied mainly at the ␤-globin locus (3,5,7).…”
Section: Expression Levels Of Hes1 During Erythroid Cell Differentiatmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides their roles in the differentiation of specific lineages of hematopoietic cells, the Ikaros family members were recently reported to be involved in the apoptosis of hematopoietic cells (19). For example, bone marrow erythroid cells derived from Ikaros-null mice are more resistant to apoptosis than those from wild-type mice (19).…”
Section: Discussionmentioning
confidence: 99%
“…Besides their roles in the differentiation of specific lineages of hematopoietic cells, the Ikaros family members were recently reported to be involved in the apoptosis of hematopoietic cells (19). For example, bone marrow erythroid cells derived from Ikaros-null mice are more resistant to apoptosis than those from wild-type mice (19). Aiolos, another member of the Ikaros family, has also been reported to control T-cell death by upregulating the expression of Bcl-2 (20), which is consistent with the present observation that IK1 regulates the expression of the apoptosis-associated protein caspase-9.…”
Section: Discussionmentioning
confidence: 99%